La venida del reino: religión, evangelización y cultura en América ; siglos XVI-XX - Ramos Cárdenas, Gabriela; Alberro, Solange; Ramos Cárdenas, Gabriela (Cuadernos para la historia de la evangelización en América Latina, 1994)
"Historical essays exploring the interaction of European Catholicism and native American peoples include considerable archival research while pursuing a diversity of topics"--Handbook of Latin American Studies, v. 58